Entrepreneurial Interest Determinants of Padangsidimpuan State Institute for Islamic Studies (IAIN) Students - Cahyani, Utari Evy (Institut Agama Islam Negeri Madura, 2020)
People assume that entrepreneurship is not a prestigious prefession to pursue. This results the entrepreneurial interest among students or college graduates is still low. This study aims to know the effect of personality, motivation, environment and education variables on the entrepreneurial interest of IAIN Padangsidimpuan students. Entrepreneurial interest variable is a categorical variable, they were the students who have an interest in entrepreneurship (1) and do not/don not have an interest in entrepreneurship (0). Data analysis methode used is logistic regression. The results of logistic regression analysis showed that variables influenced entrepreneurial interest of the students is education. According to the study results, the recommendation submitted to IAIN Padangsidimpuan is to improve the entrepreneurship education includes promoting the spirit of entrepreneurship through education in the classroom, field work, and seminars.